The Doctrine of Comparative Cost - Mason, Edward S. (Quarterly Journal of Economics, 1926)
I. The value problem in international trade theory, 63. — II. Relation of real costs to value in general theory and in the theory of international trade, 65. — The importance of a unit of measurement of real costs. 66. — III. Position of the doctrine of comparative cost in international trade theory, 72. Treatment by Ricardo and Mill of the relation of real costs to value, 72. — IV. Cairnes and the doctrine of non-competing groups, 77. — Importance of this for the doctrine of comparative cost, 81. — V. Treatment by Bastable and Marshall of therelation of real costs to value in value theory and in the theory of comparative cost, 83. —V I. Summary and conclusion, 92.